2015
DOI: 10.4317/medoral.20581
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Royal Jelly on new bone formation in rapid maxillary expansion in rats

Abstract: BackgroundThe aim of this study was to evaluate the effects of long and short term systemic usage of royal jelly on bone formation in the expanded maxillary suture in a rat model.Material and MethodsTwenty eight Wistar albino rats were randomly divided into 4 equal groups: Control (C); Only Expansion (OE), Royal Jelly (RJ) group, Royal Jelly was given to rats by oral gavage only during the expansion and retention period; Royal Jelly plus Nursery (RJN) group, Royal Jelly was given to rats by oral gavage during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
(29 reference statements)
2
13
0
Order By: Relevance
“…The amount of new bone formation and capillary intensity were increased in the shilajit group relative to the OE group. These results are in agreement with another researchs that used antioxidants and found that increase in bone formation (1,14,15,25). In contrast to previous studies (14,15), there was no significant difference for the inflammatory cell infiltration between the groups in our study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The amount of new bone formation and capillary intensity were increased in the shilajit group relative to the OE group. These results are in agreement with another researchs that used antioxidants and found that increase in bone formation (1,14,15,25). In contrast to previous studies (14,15), there was no significant difference for the inflammatory cell infiltration between the groups in our study.…”
Section: Discussionsupporting
confidence: 92%
“…We preferred rat model for experimental maxillary expansion in this study similar to previous studies (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Altan et al (14) reported that rats and rabbits were well-established animal models for showing the changes in the midpalatal suture under forces.…”
Section: Ne Group Oe Groupmentioning
confidence: 59%
See 1 more Smart Citation
“…In studies, the authors preferred a 5-day expansion period and 12-day retention period. 5,6,17,18 In the present study, the force (50 g) applied to separate the midpalatal suture and expansion/retention times was compatible with the literature.…”
Section: Discussionsupporting
confidence: 89%
“…Deynek and Ramoğlu 19 reported that the preferred amount of force for the purpose of separating the midpalatal suture in rats is between 50 and 70 grams. In studies, the authors preferred a 5‐day expansion period and 12‐day retention period 5,6,17,18 …”
Section: Discussionmentioning
confidence: 99%